Spatial price transmission and market integration of Cistanthera papaverifera (A. Chev.) in urban and rural sawn-wood markets, Delta state, Nigeria (2014)
The study examined the trend in prices of Cistanthera papaverifera species of sawn-wood in urban and rural sawn-wood markets in Delta State, Nigeria. Secondary data on dimensions {2”×2”×16 (0.013m3) 2”×3”×16 (0.019m3) and 2”×4”×16 (0.025m3)} of Cistanthera papaverifera species of sawn-wood monthly prices spanning 2004 to 2013 were sourced from sales receipt of sawn-wood sellers. The data were analyzed using Augmented Dickey Fuller (ADF) Test, Ravallion – IMC and Error Correction Mechanism test. Results revealed that price series in all the markets accepted the null hypothesis of non- stationarity at their levels at 1% and 5% significance level. The integration test revealed that the markets for all the dimensions of C. papaverifera species of sawn-wood considered were integrated in the long run. The Index of Market Concentration (IMC) indicates that the markets exhibit high short run market integration. The Error correction mechanism result indicated that the rates of price transfer were generally fast. This study concludes that sawn-wood marketing in Delta State have a high degree of market efficiency and recommends the provision of incentives to encourage tree planting as well as sustainable timber harvest and a greener environment.